새로운 약물전달체계 회사 데이터베이스의 구축 - 한인구; 정혜선 (한국약제학회, 2008)
Drug delivery systems (DDS) have entered mainstream in the pharmaceutical industry in the recent years. Major pharmaceutical companies as well as small or medium-sized biotechnology companies are developing various DDSbased products. We have established Drug Delivery System Company Database, which is an online searchable database of companies that develop DDS-based products and technologies or supply formulations and/or materials. Company summary, products and key technologies are listed in the database. DDS technology fields also include administration routes and indications of drugs. DDS terminologies, Statistical analysis, Useful Links, Glossary and Comments pages are also provided.